Homegrown Values and Hypothetical Surveys: Is the Dichotomous Choice Approach Incentive-Compatible? - Cummings, Ronald G.; Harrison, Glenn W. (American Economic Review, 1995)
The use of dichotomous choice (DC) methods has become increasingly common in applications of the contingent-valuation method (CVM)1 to elicit the that an individual might have for nonmarket environmental goods.2 This hypothetical DC method involves a subject responding yes or no to a hypothetical question that asks whether or not he would be willing to make a commitment to pay some stated amount contingent upon the provision of an environmental good. The growing use of this method is primarily based on the assumption that the method yields incentive-compatible results. This implies that subjects will answer the CVM's hypothetical question in the same way as they would answer an identical question asking for a real economic commitment and that, therefore, the hypothetical DC method will result in accurate estimates of true willingness to pay. Explicit or implicit acceptance of this assumption is seen in a number of recent studies. For example, the use of the DC method in CVM studies is strongly recommended by a panel3 convened by the National Oceanic and Atmospheric Administration (NOAA) of the United States Department of Commerce to examine the use of hypothetical CVM survey questions (see NOAA, 1993 pp. 4608, 4608, 4612). The hypothetical DC method has been used by the Attorney General of the State of Alaska in a major application of the CVM to assess damages caused by the Exxon Valdez oil spill of 1989 (see Richard T. Carson et al., 1992). A major CVM study of potential environmental damages due to proposed mining activity in the Kakadu Conservation Zone of Australia employed the DC method with a similar rationale (see David Imber et al., 1991 p. vi). It is clear that if a subject perceives that his expected utility is affected by the possibility of the good actually being provided he has no incentive to misrepresent. We can presume that in an application of a real DC method, where payment and provision of * Cummings: Policy Research Center, College of Business Administration, Georgia State University, Atlanta, GA 30303-3083; Harrison and Rutstr6m: Department of Economics, College of Business Administration, University of South Carolina, Columbia, SC 29208. We are grateful to Peter Bohm, Bengt Kristr6m, and three referees for helpful comments. Ashley Abbott, Lloyd Brown, Colin Day, Tanga McDaniel, Helen Neill, and Melonie Williams provided excellent research assistance. We acknowledge financial support provided by the State of New Mexico's Waste Management Education and Research Consortium and Resources for the Future. We retain responsibility for all errors. 'For a critical review of the debate over the CVM, see Cummings and Harrison (1994) 2Homegrown is a term primarily used in experimental economics. It refers to a subject's value that is independent of the value which an experimenter might induce for the good (see Vernon L. Smith, 1976). The idea is that homegrown values are those that the subject brings to an experiment. 3Consisting of Kenneth Arrow (Co-chair), Robert Solow (Co-chair), Paul R. Portney, Edward E. Leamer, Roy Radner, and Howard Schuman.